La vulnérabilité stratégique des minéraux : les relations triangulaires entre la République fédérale allemande, l’Afrique du Sud et l’Union soviétique. - Cooper, Andrew; Kapur, Ashok (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
Resource diplomacy has emerged as a key element in international relations. The controversy over the use of the grain embargo and persistent concern about the Middle East has allowed food and oil to continue to gain a great deal of attention as weapons of resource diplomacy. Other raw materials, nevertheless, also lend themselves to analysis of this sort. Strategic minerals, in particular, have been increasingly looked at as means of influence in both North/South and the East I West contexts. This study hopes to contribute to this growing body of literature by examining the significance (and merger) of the North/South and East I West contexts in regard to strategic minerals with particular reference to the Federal Republic of Germany. The paper examines the triangular relationship in strategic minerals between the FRG, Southern Africa and the Soviet Union. A number of scenarios have been put forward pertaining to a Soviet threat to Western mineral imports from Southern Africa. The most plausible of these scenarios appears to be that rather than the Soviets initiating action in Africa they respond to events in order to undermine confidence in the West. Such a scenario has serious implications for the FRG. Still, our tentative findings are that dire forecasts about a Soviet stranglehold on the FRG in terms of minerals are overplayed. It is suggested that coping mechanisms do exist for the FRG's supplies of raw materials.